Cretaceous Limestone Dolomitization and Argument of Its Mg2+ Sources: Exampling the Bekhme and Qamchuqa Formations in the Zagros Collision Belt - Karim , Kamal Haji; Mohamad, Sherzad Tofiq (Kurdistan Journal of Applied Research, 2024)
This study unveils new considerations regarding the dolomitization of the Bekhme and Qamchuqa formations (BQFs), two reefal Cretaceous units in the Iraqi Zagros collisional belt. Previous studies proposed the dolomitization of these formations due to the ascent of Mg-rich hydrothermal solutions through deep faults but lacked substantial supporting evidence. This paper present new considerations suggesting that the dolomitization of the BQFs resulted from the Cretaceous environmental conditions and basin paleogeographic setting of the platform on which these formations were deposited. To justify this consideration, seven proofs presented. First is the occurrence of dolomite as vast layers extending tens of kilometers laterally and bounded between limestone beds, which resemble a strata-bound occurrence. Second is the absence of vertical selective dolomitization such as, hydrothermal mineralization, vertical dolomite dykes, hydrothermal vents, tubes, or zones. Third is the barrenness of most of the fault surfaces and their surrounding rocks with selective dolomitization. Fourth is the sharp boundary between the dolomite and limestone layers, indicating a sudden environmental change from lagoon to reef or forereef. Fifth is the record of dolomitization in the sediments reworked by bioturbation, evident in thalassinoides burrows. Sixth is the succession of BQFs underlain by limestone and green marl devoid of dolomitization and hydrothermal upward movement. Seventh is the contradictory notion of hydrothermal dolomitization among the most recent study published in the Science journal which atributed dolomitization to normal temperate on earth surface. In the present study, the source of the Mg is argued and its presence is attributed to the warmth of the Arabian platform (plate) near the equator during the Cretaceous period. Another source is the connection of the Arabian platform with the Neo-Tethys Sea, which was the locus of Mg-rich mafic volcanism in the form of arcs and mid-oceanic ridge topography, which supplied a voluminous amount of Mg to the Arabian carbonate platform through ocean currents.